Factors That Affect The Increasing Visual Impairment In Children - Andy Surjadihardja; M. Ali Sodik; Amarin Yudhana; Sari, Dhita Kurnia (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2020)
The use of digital devices (smartphones, tabs and laptops) can result in a sharp decrease in vision in children, especially during the covid 19 pandemic. this will result in visual impairment or anomaly refractive one of them myopia.  The Research Purpose is to determine the influence of the use of digital devices (smartphones, tabs and laptops) on the increasing visual impairment or Anomaly refraction in school-age children (12-14 years) at Optik Melawai, Galaxy Mall Lt. 1 no. 103-104 Jl. Dharma Husada no. 35-37 Surabaya. Research using observation analysis, samples taken based on the results of eye examinations, interviews and questionnaires for 3 months, namely September 2020 to November 2021 with the number of patients as many as 75 children. With the study subjects as many as 75 children, with age 12-14 years, among them 48 boys and 27 girls, after examination 100% impaired vision or anomaly refractive and In this study limited only anomaly refractive myopia. The use of digital devices (smartphones, tablets and laptops) can result in visual impairment or anomaly refractive myopia in children.